Randomized clinical trial on efficacy of fixed-dose efavirenz/tenofovir/emtricitabine on alternate days versus continuous treatment. (1st March 2019) - Bellagamba, Rita; Giancola, Maria Letizia; Tommasi, Chiara; Piselli, Pierluca; Tempestilli, Massimo; Angeletti, Claudio; Zaccarelli, Mauro; Ammassari, Adriana; Pinnetti, Carmela; Gallo, Anna Loredana; Antinori, Andrea; Narciso, Pasquale; et al.
Abstract : Objective: Antiretrovirals with long half-lives, such as tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) and efavirenz (EFV), are suitable for reduced frequency dosing, with potential for improved adherence and reduced toxicity and costs. The objective of this study was to investigate the noninferiority of the TDF/FTC/EFV fixed-dose combination on alternate-days versus standard regimen in virologically suppressed patients. Design: A randomized-controlled open-label noninferiority trial enrolling HIV-1-infected patients treated for at least 6 months with TDF/FTC/EFV fixed-dose combination, virologically suppressed (<40 HIV-RNA copies/ml) with EFV plasma concentrations greater than 1000 ng/ml, were randomized to maintain TDF/FTC/EFV standard-of-care regimen (SOC, Arm A) or to switch to TDF/FTC/EFV on AlTernAte Days (ATAD, Arm B). Methods: Primary end-point was the proportion of patients with less than 40 HIV-RNA copies/ml at week 48. Results: One hundred and ninety-seven patients were randomized (98 in the SOC and 99 in the ATAD arm). One hundred and seventy-nine (90.3%) were men, median age 43.2 years, 133 (67.5%) MSM. CD4 + T-cell count at baseline was 706 cells/μl in SOC and 632 cells/μl in ATAD arm. At week 48, 95 (96.9%) patients in SOC and 93 (93.9%) in ATAD had a virological response (−3.0% overall risk difference, 95% CI: −8.86%/2.86%). Median change from baseline at week 48 in CD4 + T-cell count was 29.4 cells/μl (95% CI: 2.5/56.4) in SOC ( P = 0.008) and 61.0 cells/μl (95% CI: 32.1/89.9) in ATAD ( P < 0.001). Median change of EFV concentration at week 48 from baseline was −6.5 ng/ml (95% CI: −103/55) in SOC ( P = 0.877) and −1124 ng/ml (95% CI: −1375/−928) in ATAD arm ( P < 0.001). Conclusion: Despite a significant decrease of EFV exposure, TDF/FTC/EFV on ATAD was noninferior to SOC regimen through 48 weeks. Abstract : Supplemental Digital Content is available in the text